Plant growth-promoting bacteria from Uzungöl forest stimulate rice growth via seed biopriming and root inoculation: isolation and functional characterization of potent PGPR strains from rhizosphere soils of different trees - Ishaq, Saad; Belduz, Ali Osman; Ceylan, Esma; Senocak, Aleyna Nalcaoglu; Munawar, Wajeeha; Alkowlani, Amir Towfiq Hasan; Terzi, Rabiye; Bektas, Kadriye Inan; Canakci, Sabriye (Frontiers in Plant Science, 2025)
IntroductionRhizobacteria naturally promote plant growth and offer a sustainable alternative to agrochemicals. In contrast to agroecosystems, forests host a diverse community of beneficial rhizobacteria that remains uncharacterized. Moreover, despite extensive research on rhizobacteria associated with cereal crops, such as rice, their efficacy in hydroponic rice cultivation still needs to be established.MethodsThis study was aimed to isolate, characterize, and identify the potential plant growth-promoting rhizobacteria (PGPR) of different rhizospheres from Uzungöl forest situated in Trabzon, Turkey, and to evaluate their effects on the growth of rice through two distinct approaches: 1) seed biopriming to assess germination and 2) root inoculation to analyze seedling growth in a hydroponic system.ResultsIn total, 129 bacteria were isolated from eight different rhizospheres, and 109 exhibited indole-acetic acid (IAA) production. A strain of Bacillus altitudinis from the Acer pseudoplatanus rhizosphere produced the highest (739.9 ± 251.5 µg/mL) IAA. Siderophore formation was exhibited by 16 isolates including the strains of Lysinibacillus fusiformis, Microbacterium phyllosphaerae, and Lelliottia sp. Phosphate solubilization was observed only in nine isolates including the strains of Acinetobacter calcoaceticus and Lelliottia sp. Furthermore, 65 isolates including the strains of Herbaspirillum huttiense, Lelliottia amnigena, Bacillus altitudinis, and A. calcoaceticus were identified as potential endogenous nitrogen-fixing diazotrophs for rice. Various isolates exhibited salt tolerance, HCN, ammonia, and hydrolytic enzyme production. Several of these PGPR strains as well as the strains of Viridibacillus arenosi, Psychrobacillus faecigallinarum, Bacillus siamensis, Micrococcus luteus, and Staphylococcus succinus demonstrated positive effects on rice germination or seedling growth. Herbaspirillum huttiense strain S1(E) from Abies nordmanniana rhizosphere and Pseudomonas mohnii strain SS7(5) from Malus domestica rhizosphere exhibited outstanding response as seed biopriming agents and root inoculants for rice.DiscussionThese findings concluded that inoculation with forest-derived rhizobacteria is an effective strategy to enhance early growth of rice in soilless systems. Understanding the genetic basis of their growth promotion, coupled with large-scale field validation, could advance low-cost, sustainable rice cultivation with minimal reliance on agrochemicals.